Modulation of bactericidal action in polymer nanocomposites: light-tuned Ag+ release from electrospun PMMA fibers. Issue 81 (16th August 2016) - Moreno, I.; Navascues, N.; Irusta, S.; Santamaria, J.
Abstract : Silver rate release from electrospun PMMA fibers tuned by combination of silver ions and silver nanoparticles produced by UV irradiation. Abstract : While silver is widely regarded as a potent antibacterial material, controlling the rate of release of the bactericidal agents (silver ions) remains a challenge. When silver nanoparticles are used as precursors, the release process involves oxidation and dissolution in the surrounding environment. Here we show that it is possible to tune the rate of silver release from polymer matrices containing silver precursors by a simple UV irradiation step. To demonstrate this, silver-containing polymer (PMMA) fibers have been produced by electrospinning, then subjected to different levels of exposure to UV radiation and fully characterized in terms of silver state, presence of nanoparticles, Ag + release rates and bactericidal power. The as-spun fibers contained mainly silver as Ag +, while samples exposed to UV radiation displayed progressively higher proportions of Ag 0 (XPS analysis). Nanoparticles consisting of metallic silver were present in UV-exposed samples, and their size increased with irradiation time. The Ag + release rates (and the bactericidal action of the nanofibers) were found to directly depend on the degree of UV exposure: a fast Ag + release was observed for non-irradiated samples, which during the release experiment delivered roughly three times as much silver than samples subjected to 24 h UV exposure.